Maritime Logistics, Geo-Economic Integration, and Economic Rent Capture in The Malacca Strait: Implications for Indonesia’s Maritime Competitiveness - Ferry Noldy Langelo; Citra Aprilia (CV. Publikasi Indonesia, 2026)
This study examines economic rent capture and maritime competitiveness within Southeast Asian economies along the Malacca Strait, a key global trade and energy corridor. While previous research emphasizes maritime security and geopolitical rivalry, this study focuses on maritime economic integration and value distribution among littoral states. A mixed-method approach combining geopolitical economy analysis with panel data assessment was employed, covering 2010–2024. Key indicators include port throughput, logistics performance, trade integration, and maritime industrialization, compiled from UNCTAD, World Bank, IMF, ASEAN reports, and national statistics. Findings show that maritime competitiveness increasingly relies on logistics integration, institutional efficiency, digital maritime systems, and industrial ecosystem development rather than geographic location alone. Panel regression results indicate that logistics performance and maritime industrialization significantly enhance economic outcomes among Southeast Asian maritime economies. Despite Indonesia’s geographic advantage within the Strait, its economic value capture remains constrained by fragmented logistics, limited integration of maritime services, and uneven industrial coordination. This study contributes to the literature by integrating maritime geopolitics, logistics governance, and geo-economic perspectives in a unified framework. It proposes a strategic policy framework emphasizing maritime industrialization, smart-port integration, logistics sovereignty, and ecosystem-based maritime development to enhance Indonesia’s competitiveness within the evolving Indo-Pacific economy.